Analysis of composite bonded joints - Chui, Christopher Shao Liang (2017)
Two simple strong and stiff fiber reinforced polymer matrix composite laminate components (adherends) could be joined using polymer resins (adhesive) to realise a complex structural member. The advantage of using adhesive bonding over mechanical fasteners includes better strength to weight ratio, greater design flexibility, ease of manufacturing and crucially preventing the formation of stress concentrators during the drilling which promotes premature failure. Thus, there has been an increased us of adhesive joints in the aerospace industry for manufacturing and repair purposes. This parametric study on adhesive bonded composite single lap joints aims to determine the optimum bondline thickness, bond length and dimensions of a hybrid single lap joint, which gives the highest ultimate shear strength under a lap shear test in accordance to ASTM D5868. Film adhesive SA 80 was primarily used in all three experiments and the thickness is varied by placing 1, 3 and 5 layers of SA 80, while the bondline thickness is controlled by the length of the film adhesive used, and we investigated bond lengths of 25.4mm, 50.8mm and 76.2mm. The samples in each experiment were subjected to a lap shear test, micrograph for failure mode analysis and finite element analysis (ABAQUS) to understand the stress variation within the bond length.